2015
DOI: 10.1111/geb.12413
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting beta diversity among regions: how do classical and multivariate approaches compare?

Abstract: Aim Approaches to calculating beta diversity (β) include classical measures based on alpha (α) and gamma (γ) diversity, and multivariate distance-based measures. Species-area relationships cause measurements of γ to vary, making comparisons of classical β among regions contingent on sampling effort. A recent null-modelling approach has attempted to account for variation in γ by calculating the degree to which β deviates from a random expectation. Here, we clarify the mathematical links between classical and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
111
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(116 citation statements)
references
References 57 publications
3
111
2
Order By: Relevance
“…These results were consistent with the full dataset and when late June samples were omitted (P < 0.001 in both cases). The complementary metric, pairwise dissimilarity (Bennett & Gilbert 2016), also indicated that flowers exposed to pollinators had a higher average dissimilarity between samples than those from caged and bagged treatments (Tukey HSD P < 0.0001 for all comparisons; Fig S6). Fungal composition varied primarily among months (P < 0.001), but with late June samples omitted, exposed flowers had higher fungal beta diversity than caged flowers (beta diversity P = 0.04, Fig.…”
Section: Species Diversitymentioning
confidence: 94%
“…These results were consistent with the full dataset and when late June samples were omitted (P < 0.001 in both cases). The complementary metric, pairwise dissimilarity (Bennett & Gilbert 2016), also indicated that flowers exposed to pollinators had a higher average dissimilarity between samples than those from caged and bagged treatments (Tukey HSD P < 0.0001 for all comparisons; Fig S6). Fungal composition varied primarily among months (P < 0.001), but with late June samples omitted, exposed flowers had higher fungal beta diversity than caged flowers (beta diversity P = 0.04, Fig.…”
Section: Species Diversitymentioning
confidence: 94%
“…We calculated the beta diversity between pairs of communities (2°9 2°grid cells) for each region following the approach proposed by Baselga (2010). According to current literature, pairwise measures of beta diversity are the best way to avoid biases related to sample size differences when comparing beta diversity between regions (Bennett & Gilbert, 2016). Taxonomic and phylogenetic beta diversity components were calculated using Simpson dissimilarity for the turnover component and a Sorensen-derived formula for the nestedness/richness difference component in the R package 'betapart' (Baselga & Orme, 2012) using the functions beta.pair and phylo.beta.pair, respectively (the equations used in our study are provided in the supplementary material, but see Baselga (2010) for a broad explanation regarding the equations we used for taxonomic beta diversity and Leprieur et al (2012) for explanations of the equations used for phylogenetic beta diversity).…”
Section: Beta Diversitymentioning
confidence: 99%
“…Comparing β -diversity, the variation in species composition, among different regions is an important yet controversial topic in ecology (Kraft et al, 2011; Qian, Chen, Mao, & Ouyang, 2013; Bennett & Gilbert, 2016; Ulrich et al, 2017). A randomization-based null model that was said to correct for the dependence of raw β -diversity on species pool (Kraft et al, 2011) has been widely adopted for this purpose (e.g., De Cáceres et al, 2012; Myers et al, 2013; Vannette & Fukami, 2017; Xing & He, 2019; Zhang, He, Zhang, Zhao, & von Gadow, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A randomization-based null model that was said to correct for the dependence of raw β -diversity on species pool (Kraft et al, 2011) has been widely adopted for this purpose (e.g., De Cáceres et al, 2012; Myers et al, 2013; Vannette & Fukami, 2017; Xing & He, 2019; Zhang, He, Zhang, Zhao, & von Gadow, 2020). However, this randomization approach has been criticized on several aspects, including incorrect interpretations of the β -deviation metric and the dependence of the metric on sampling effort and species pool (Qian et al, 2013; Bennett & Gilbert, 2016; Ulrich et al, 2017, 2018). Another limitation of the null model is that it requires individual-level data and thus limits its application to situations when only abundances of individual species in each local community are available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation